The Effect of Media Convergence on Exploitation of Entrepreneurial Opportunities (2019)
This paper sheds light on specific aspect of Media Convergence which is not only about convergence and similarity, but about divergence in different aspects and opportunities which bring up for entrepreneurial activities. Problem area of this study is to understand how media convergence provides new business opportunities in media markets and how media entrepreneurs can exploit those opportunities for proposing value to target customers. This paper follows a quantitative research design. Therefore, 119 cofounders of small and medium media firms answered an online questionnaire, and the data was analyzed by SPSS. Regression analysis was used to analyze the data. The findings reveal that four types of divergence, including media distribution channels, media content producers, audiences, and advertisers, affect exploitation of entrepreneurial opportunities in small and medium sized media firms.